2015
DOI: 10.1097/sap.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Long-Term Follow-Up of Oral Cancer Postoperative Sialorrhea With Dermal Sling Operation

Abstract: The dermal sling operation is an acceptable treatment for postoperative sialorrhea in patients with commissure-involved oral cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that tongue treatment increases food residue in the oral cavity [11]. Oral morphological changes are known to cause sialorrhea by reducing the ability of the mouth to retain saliva [12]. It is also widely known that resection of the tongue results in organic articulation disorders, which makes it difficult to improve function to the preoperative level because it is caused by organic changes [13].…”
Section: Oral Hygiene Typementioning
confidence: 99%
“…It has been reported that tongue treatment increases food residue in the oral cavity [11]. Oral morphological changes are known to cause sialorrhea by reducing the ability of the mouth to retain saliva [12]. It is also widely known that resection of the tongue results in organic articulation disorders, which makes it difficult to improve function to the preoperative level because it is caused by organic changes [13].…”
Section: Oral Hygiene Typementioning
confidence: 99%
“…Even in the presence of normal saliva volume and consistency, RT can cause fibrosis and poor function which can lead to poor control of saliva impacting further on patients overall QOL. There exists only a few questionnaires that specifically ask about the issue of too much saliva for example Groningen radiotherapy-induced xerostomia (GRIX) questionnaire (Beetz et al, 2010), Drooling Severity and Frequency Scale (Li et al, 2015), Liverpool Oral Rehabilitation Questionnaire (LORQ) (Pace-Balzan, 2008).…”
Section: Introductionmentioning
confidence: 99%